Prevalence of cardiovascular risk factors in postmenopausal women: A rural study - Vishal R Tandon; Annil Mahajan; Sudhaa Sharma; Anil Sharma (Wolters Kluwer Medknow Publications, 2010)
Aim: The present observational, cross-sectional prospective study was conducted during the period of 1 year in one of the rural health centers to study prevalence of conventional cardiovascular disease risk factors (CVRFs) in postmenopausal women. Materials and Methods: Five hundred consecutive postmenopausal women were screened for detailed information regarding common menopausal symptoms, the presence or absence of conventional CVRFs. Physical activity was measured, and dietary lifestyle was also assessed. Use of hormone replacement therapy (HRT) and other drugs were also noted. Knowledge regarding their menopause was also evaluated. Results: Mean age at menopause was 49.35 years, Mean number of menopausal symptoms was 6.70 ± 5.76, and mean duration since menopause was (MDSM = 4.70 years)). Fatigue, lack of energy (70%), cold hand and feet, rheumatology-related symptoms (60%) cold sweats, weight gain, irritability, and nervousness (50%), palpitation of heart, excitable/anxiety (30%) each were common complaints. Hypertension was diagnosed or a person was a known hypertensive (56%). Diabetes was diagnosed or a person was known diabetic in 21%, and BMI was found to be 25 kg/m 2 in 78%. Truncal obesity with waist-hip ratio >0.8 in 68% females, whereas abdominal obesity with waist size >88 cm was in 60% women. Dyslipidemia was seen in 39%. It was defined by the presence of high TC (=200 mg/dL) in 30%, high LDL-c (=130 mg/dL) in 27%, low HDLc (<40 mg/dL) in 21% or high TG (=150 mg/dL) in 31%. Metabolic syndrome was present in 13% of cases. CRP was found positive in 12 out of 39 total evaluated women, and serum uric acid was found >6.5 mg/dL in 4%. Smoking (0.5%), alcohol (0%,), tobacco chewing (4%), and family history of premature heart disease (9%) were recorded. Lifestyle was active in 35%, hectic in 10%, and sedentary in 55% of postmenopausal women (PMWs). Only 5% of women were receiving HRT, 0.5% isoflavone-containing phytoestrogens, 0.4% tibolone, 24% anti-HT, 9% anti-diabetic, 8% lipid-lowering drugs, and only three patients were on anti-obesity along with dietary and lifestyle management. Out of 68 patients, who were advised for electrocardiography (ECG), 23 were found positive for ischemic changes on ECG and out of 12 women advised for treadmill test (TMT), only four were found positive for ischemic heart disease (IHD). Risk factor count of more than four was found in 11%. Over all 96% of women were affected by menopause or related problems. Only 9% were aware about their menopause, 3% for importance of lifestyle modification, weight and dietary management programs to ameliorate menopause or menopause-compounded CVRFs. Conclusion: This study showed alarmingly high prevalence of most of the conventional CVRFs, especially diabetes, hypertension, dyslipidemia, obesity, and other risk factors in postmenopausal women from rural areas.